Dynamic Pressure Manifestation Mechanism and Control Techniques for Roadways with Large Mining Heights and Intense Mining: A Case Study. (17th April 2023) - Xu, Dong; Gao, Mingshi; Yu, Xin
Abstract : Responding to severe surrounding rock deformation failures and other problems in roadways in western China with large mining heights and intense mining, the work presented in this paper studied the mechanism of surrounding rock deformation failures in roadways with dynamic pressure through field investigations, theoretical analysis, and numerical simulation. According to the research findings, mining roadway deformation failures are affected by roadway layout orientation, working face mining intensity, and dynamic load disturbances from roof breakage. Coal pillars, as bridges connecting the roof and floor, constitute the energy transfer path near roadways surrounding rock, and an unreasonable coal pillar size and lateral overhanging roof structure may aggravate static load energy accumulation in the roadway surrounding rock. Roadway protection with small or large coal pillars may increase elastic energy loss in the energy transfer path; a reasonable size of small and large coal pillars is 15 m and 35 m, respectively. Using roof cutting for pressure relief may reduce the elastic energy of roadway surrounding rock by 14.35-26.33% during primary mining and 21.57-29.31% during secondary mining, thereby reducing the static load elastic energy in the surrounding rock and improving the stability of roadway surrounding rock.